Neural circuits underlying motor facilitation during observation of implied motion. (2nd October 2015) - Concerto, Carmen; Al Sawah, Mohomad; Infortuna, Carmenrita; Freedberg, David; Chusid, Eileen; Aguglia, Eugenio; Battaglia, Fortunato
Abstract: In the present study we used single and paired-pulse Transcranial Magnetic Stimulation (TMS) to evaluate the effect of implied motion on primary motor cortex microcircuits. We found that observation of the implied motion of a static image increases MEP amplitude and reduces short-interval intracortical inhibition (SICI), without significant modulation of intracortical facilitation and sensory-motor integration. Our results add to the existing literature on the activation of the observation-execution matching system and describe a selective modulation of GABAergic cortical microcircuits during observation of implied motion.